Taking Stock of Trade Protectionism Since 2008 - Datt, Mohini; Hoekman, Bernard; Malouche, Mariem (World Bank, Washington, DC, 2012)
The onset of the financial crisis in September 2008 and the subsequent 'Great Trade Collapse' (Baldwin 2009), many countries actively used trade policy instruments as part of their response to the global recession. Governments pursued a mix of trade liberalization, trade promotion, and trade restrictions. The choice of trade policy has varied, with limited use of tariff hikes or antidumping and safeguard actions. Sector-specific support to industries dominated initial responses to the crisis, and there has been increasing resort to nontariff measures. Recent research suggests that vertical specialization the growth in global supply chains has played a significant role in limiting the use of traditional protectionist instruments. Pressures on governments to support domestic economic activity may increase, given current gloomy economic prospects and more binding macroeconomic policy constraints, and the number of protectionist measures has recently risen. Open trade cannot be taken for granted, thus the need for monitoring persists.